From Rating to Purchase Decisions: A Systematic Literature Review on Online Reviews and Consumer Behavior - Samuel Morales Simanjuntak; Siti Putri Luthfiyyah; Astrea Wulanda; Syafrizal Helmi Situmorang; Beby Karina Fawzeea Sembiring (International Journal of Economics, Management and Accounting (IJEMA), 2024)
This study aims to identify consumer behavior through bold reviews, which play an essential role in purchasing decisions. The systematic approach in this study is a significant contribution, especially in exploring aspects of tone, review length, and content quality. The Prisma model Systematic Literature Review (SLR) method is used to map 536 literatures from 2020 to 2024, with the help of VOSviewer to analyze trends and research analysis. The results show the critical role of technology, such as sentiment analysis, in understanding consumer emotions and the significant impact of reviews on consumer preferences. This study opens opportunities to explore further review elements influencing consumer purchasing decisions.